Demokracja ponadnarodowa w Unii Europejskiej. Wstępna analiza teoretyczna - Ruszkowski, Janusz (Rocznik Integracji Europejskiej, 2015)
This paper seeks answers to the following two research questions: whether it is possible to have democracy without people (here as an example of democracy at the supranational level in the EU), and what are the sources of such a democracy, if the source is not a nation, and the area is not a state? This paper provides a new approach to the theory of democracy and postulates to integrate a new type of democracy and traditional concept of democracy. The main theoretical paradigm on which the theory was based is supranationalism with elements of the theory of democracy and Multi-level Governance (MLG). Supranational democracy in the European Union is located on a supranational level of MLG, which means that it is not assigned to the state and – importantly – in practice demonstrates that it does not have to have a national character. The text presents a preliminary attempt at a theoretical analysis related to supranational democracy in the EU. In practice, the author goes towards identifying the constituent components of the concept of “supranational democracy” and the sources of this phenomenon in the European Union.